Butyrate limits human natural killer cell effector function - Vanessa Zaiatz-Bittencourt; Fiona Jones; Miriam Tosetto; Caitriona Scaife; Gerard Cagney; Evan Jones; Glen A. Doherty; Elizabeth J. Ryan (Scientific Reports, 2023)
Abstract The gut microbiota regulates chronic inflammation and has been implicated in the pathogenesis of a broad spectrum of disease including autoimmunity and cancer. Microbial short-chain fatty acids (SCFAs) e.g., butyrate have demonstrated immunomodulatory effects and are thought to be key mediators of the host-microbiome interaction. Here, we investigated the effect of butyrate on effector functions of blood derived human NK cells stimulated for 18 h with a combination of IL-12/IL-15, a potent mix of cytokines that drive NK cell activation. We show that butyrate has a strong anti-inflammatory effect on NK cells. NK cells cultured in the presence of butyrate expressed lower levels of activating receptors (TRAIL, NKp30, NKp44) and produced lower levels of cytokines (IFNγ, TNF-α, IL-22, granzyme B, granzyme A, perforin) in response to IL-12/IL-15. Butyrate restricted NK cell function by downregulation of mTORC1 activity, c-Myc mRNA expression and metabolism. Using a shotgun proteomic approach, we confirmed the effect of butyrate on NK cell cytokine signaling and metabolism and identified BRD2, MAT2A and EHD1 as downstream mediators of these effects. This insight into the immunomodulatory activity of butyrate on human NK cell function might help to develop new ways to limit NK cell function during chronic inflammation.